2018
DOI: 10.1080/00224499.2018.1433287
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and Adapting a Conceptual Model of Sexual Positioning Practices and Sexual Risk Among HIV-Negative Black Men Who Have Sex With Men

Abstract: Estimates show a 50% lifetime human immunodeficiency virus (HIV) risk among Black men who have sex with men (BMSM) in the United States(U.S.). Studying the dynamics of sexual positioning practices among BMSM could provide insights into the disparities observed among U.S. groups of men who have sex with men (MSM). This study explored sexual positioning dynamics among HIV-negative BMSM and how they aligned with a theoretical model of sexual positioning and HIV/sexually transmitted infection (STI) risk among MSM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Yet, our formative research, in conjunction with our practical experience managing a large HIV testing program, also suggested that self-testing could be an empowering option that could support autonomy and reduce anxiety associated with contact with inhospitable or unsafe service contexts [ 27 ]. Moreover, a peer-based self-testing approach builds disclosure of a positive test result to a supportive social network member into the testing process [ 34 36 ]. Given that social support is associated with linkage to care and HIV testing, building social support into rapid self-testing may also increase likelihood of care linkage [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, our formative research, in conjunction with our practical experience managing a large HIV testing program, also suggested that self-testing could be an empowering option that could support autonomy and reduce anxiety associated with contact with inhospitable or unsafe service contexts [ 27 ]. Moreover, a peer-based self-testing approach builds disclosure of a positive test result to a supportive social network member into the testing process [ 34 36 ]. Given that social support is associated with linkage to care and HIV testing, building social support into rapid self-testing may also increase likelihood of care linkage [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…MSM may intentionally use alcohol and/or other substances to enhance sexual pleasure, ease physical pain, or to cope with psychological distress related to being the receptive partner (Collier et al., ; Damon and Simon, ; Dangerfield et al., ; Simon et al., ). Although the frequency of alcohol use before/during sex failed to significantly predict condom use in the present study, it is interesting to consider the ways in which intentional alcohol use to facilitate sexual enjoyment may, over time, increase the overall frequency of alcohol use and contribute to the development of alcohol use problems and/or alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Substance use among MSM has been associated with coping with stigma, reducing pain from receptive anal sex, facilitating group sex, transactional sex and multiple partnerships (27,28). The use of substances during sex affects judgement and increases the likelihood of high-risk sexual practices such as condom-less sex (9,29,30). MSM who engaged in transactional sex were more likely to report sexual violence and assault but showed no difference in condom use compared to MSM who did not in a study conducted in Nigeria (24).…”
Section: Introductionmentioning
confidence: 99%